Planowanie międzynarodowe i jego rola w integracji krajów RWPG - Guzek, Marian (Wydział Prawa i Administracji UAM, 1970)
Considering the possibilities of improving the planning links among the member- -states of the Council for Mutual Economic Assistance, the author distinguishes three forms of the international scale planning activities: 1) modified coordination of national economic plans; 2) programming of the international division of labour; 3) joint economic planning. The article deals with the third form which is considered to be the most controversial one. Two extreme views known from the literature are critically examined. The first one treats the joint planning as a supra-national activity based on the rules of directive planning and therefore unrealistic. The second one acknowledges the present coordination procedure as a sufficient symptom of the joint planning. Considering this view as inadequate, the author makes an attempt to formulate the rules of indirect international planning. He suggests that such a form of planning would not require supra-national authority. It has been presumed, however, that an international planning centre representing the member-states might modify the actual institutional and economic conditions and introduce a coherent system of stimula promoting the implementation of the joint plan. Besides, the assumption was made that the plan itself would have to be ratified by the member-states.
International Planning and its Role in the CMEA Integration